The exploitation of “Grade of Membership (GoM) model” and “Combined Analysis method” in analysing of urban dynamics and urban hierarchy in Khorasan region (1956-2016) - Tahmoores Behrouzinia (تحقیقات کاربردی علوم جغرافیایی)
Concerning the importance of urban network studies and the role of hierarchy system in population decentralization in metropolitan areas, this paper by using acknowledged indicators and Grade of Membership (GoM) model and using Combined Analysis method has tried to find the changes in urban hierarchy of Khorasan region during the period 1956-2016. The outcomes show that urban system in Khorasan region as the one in the country was afflicted with inconsequentiality by 1986. However, during the period 1986-2006, the urban network in Khorasan region tended to reach to an equilibrium. Nevertheless, it has gone toward an imbalance during the period 2006-16. The outcomes also depict that the models and indicators did not work coordinated. While some indicators (such as Herfindahl and Entropy indexes) showed that, there were an equilibrium among the urban network in the region, some other (such as Primate City and Centrality indicators) showed increasing centralization and inconsequentiality. Accordingly, the study used “GoM model” and “Combined Analysis method” for the final analysis. The GoM used three variables that aimed to make the model more reliable: The Prime City Indicator, the Centrality Indicator and Equilibrium Indicator. With this methodological novelty, the analysis of the hierarchical patterns represented in the model by the multiple profiles were closer to what could be understood as a "methodological ideal", difficult to be applied empirically due to the complexity of the subject, but included in studies theoretically based. As for future studies, which will seek to understand the hierarchical urban organization of other regions of the country and of the world, these indicators may be incorporated if adapted to the regional reality.